(untitled) (Research, Society and Development, 2020)
The presence of residues in food due to the irrational use of veterinary drugs in farm animals is recognized as a global threat to consumer health, with emphasis on bacterial resistance. Here, we present a comprehensive and not yet reported approach, with the objective of establishing a detailed critical analysis of the instructions for 433 antimicrobials for poultry, cattle and pigs marketed in Brazil, in relation to the current legislation. The frequencies of conformities were compared by the global chi-square test (X2), resulting in 78 contrasts, for each group of data, which were evaluated by approximation to normal (α=0.05). The discrimination between the frequencies was performed by studying the contrasts and by approaching the normal post hoc, using the Bonferroni correlation to estimate the critical z. There was a significant discrepancy between the different requirements (p<0.05), with information on pharmacodynamics and pharmacokinetics being considered critical, as only 1.2 % of the package inserts addressed this topic, as well as warnings, precautions, side effects, contraindications, drug interactions and antidotes; legend for veterinary use; storage conditions; and sales declaration under veterinary prescription, with 100 %, 97.9 %, 72.5 % and 80.6 %, respectively, of non-conformities. These findings reinforce the urgent need for action to meet legal requirements of the package inserts, which are undoubtedly a key point for ensuring food safety and quality.